2019
DOI: 10.1556/2006.8.2019.49
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for self-controlling social media use: Classification and role in preventing social media addiction symptoms

Abstract: Background and aims Many people present excessive patterns of social networking site (SNS) use and try to self-regulate it. However, little is known regarding the strategies employed by young adult SNS users and their role in preventing the emergence of addiction-like symptoms in relation to SNS use. Methods In Study 1, we employed a naturalistic-qualitative approach for finding commonly employed self-control strategies in relation to SNS use. In Study 2, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 33 publications
(59 reference statements)
2
51
0
1
Order By: Relevance
“…(11) However, findings of this study revealed that a significant proportion (45.5%) of participants deliberately reduced their access to COVID-19-related information due to factors such as repetitive information and tiredness, suggesting self-control strategies play an important role in the regulation of information consumption behavior. (12) Answers related to potential signs of information overload associated with the pandemic indicated that approximately one-third of respondents felt stressed by the amount of information they had to keep up with almost every day or always. Overall, more than half of respondents experienced at least one psychological distress symptom (headache, eye twitching, restlessness or trouble sleeping) and the frequency of symptoms was higher among participants with a negative bias towards excessive information processing demands.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…(11) However, findings of this study revealed that a significant proportion (45.5%) of participants deliberately reduced their access to COVID-19-related information due to factors such as repetitive information and tiredness, suggesting self-control strategies play an important role in the regulation of information consumption behavior. (12) Answers related to potential signs of information overload associated with the pandemic indicated that approximately one-third of respondents felt stressed by the amount of information they had to keep up with almost every day or always. Overall, more than half of respondents experienced at least one psychological distress symptom (headache, eye twitching, restlessness or trouble sleeping) and the frequency of symptoms was higher among participants with a negative bias towards excessive information processing demands.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…Despite its short-term success, active self-control is more difficult to maintain than altering the cues that trigger media habits, such as putting a cell phone on mute (Brevers & Turel, 2019). Furthermore, the strategy of changing cues should especially curb strongly habitual use, given that habits are activated directly by such cues.…”
Section: Controlling Social Media Habitsmentioning
confidence: 99%
“…However, these rewards also motivate occasional users of social media and lead to the formation of use habits; they are not necessarily linked to addiction. Instead, in a more informed analysis,Brevers and Turel (2019) noted that stronger habits to use social media are moderately correlated with but not identical to the severity of addiction symptoms. In their analysis, habits can become problematic and lead to addiction, but the automaticity in habit is only one component of the maladaptive overuse of social media.…”
mentioning
confidence: 96%
“…Social-virtual addictions have recently become a major concern and a common problem worldwide. The use of social networking sites (SNS), such as Telegram, Instagram, WhatsApp, YouTube, and other SNS, has dramatically changed the way people socialize, share information, work, perceive others, and present themselves (1). Moreover, SNS addiction has been introduced as a new behavioral addiction, along with increasing social network sites (2).…”
Section: Introductionmentioning
confidence: 99%